A Cross-Sectional Study of the Perception of Individualized Nursing Care Among Nurses in Acute Medical and Perioperative Settings - Ramos, Ana (2024)
Individualized nursing care allows for systematic assessment and intervention; considers a patient’s preferences, values, and context; and contributes to a positive care trajectory. However, its operationalization has proven to be challenging. This research aimed to evaluate nurses’ perceptions of individualized care and analyze their relationship with sociodemographic variables. Methods: A cross-sectional study was conducted on 122 eligible and registered nurses at a Hospital Center, in the Ophthalmology (operating room and inpatient ward) service, the Cardiology service, the Internal Medicine service, and the Medical Emergency Unit, for adults/older adults in Portugal. The nursing version of the Individualized Care Scale (ICS-Nurse) was used for the assessment, including three sub-dimensions: clinical situation, personal life situation, and decisional control over care-related decisions. Cronbach’s alpha and principal component analysis were used for the data analysis. The STROBE checklist was used to report this study. Results: No statistically significant differences were found based on the age, gender, level of education, or years of professional experience of the nurses within the sub-dimensions of individualization. The nurses overall had a good perception of the importance of individualized care (4.06 ± 0.46 ICS-A-NURSE) but faced difficulties in its implementation during the last shift they worked (3.97 ± 0.49 ICS-B-NURSE). Conclusions: The items considered to be of greatest importance were the response to the physical and emotional needs arising from illness and assistance in decision-making through educational instructions. Aspects related to the personal lives of patients, such as family inclusion in an individual’s care plan, everyday habits, and previous experiences of hospitalization, received the lowest scores. Recognizing priority areas for improvement in the individualization of nursing care can contribute to developing training programs and policies that promote a holistic approach. Future studies should consider patient outcomes related to their needs for individualization.